2021
DOI: 10.1093/ageing/afab030.40
|View full text |Cite
|
Sign up to set email alerts
|

79 Relationship Between Depression and Nutritional Status Among the Elderly Attending Selected Primary Healthcare Centers in Lagos

Abstract: Introduction Depression causes and worsens malnutrition. The prevalence of malnutrition in the elderly of the developed world was about 22.6% and about 40% of hospitalized elderly are malnourished while about 4.8% have one major depressive episode in people aged 50 and above. Food rich in omega-3 has antidepressant effect and its low intake is linked with dementia. Decrease dietary folate has been linked with depression. This study was aimed at determining the relationship between depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, there has been a growing awareness of the importance of this fact, and every time, more hospitals are contemplating the role of nutritionists to reduce health costs. In poor infrastructure areas, it has been a cost-effective measure to warn about the struggles in the quality of life of their population, always finding an association between MDD and malnourishment ( 70 72 ).…”
Section: Nutrition Epigenetics and Mdd: Is There A Link?mentioning
confidence: 99%
“…Thus, there has been a growing awareness of the importance of this fact, and every time, more hospitals are contemplating the role of nutritionists to reduce health costs. In poor infrastructure areas, it has been a cost-effective measure to warn about the struggles in the quality of life of their population, always finding an association between MDD and malnourishment ( 70 72 ).…”
Section: Nutrition Epigenetics and Mdd: Is There A Link?mentioning
confidence: 99%
“…Studies have identified possible predisposing and enabling factors for this behavior among patients, including financial challenges, long hospital waiting times, poor understanding of the health system, and poor knowledge about their medical conditions and reason for referral 13,14 . Notwithstanding, Akodu et al 20 reported an overall high satisfaction level with the quality of service received among elderly patients attending nine PHC centers in Lagos state, despite having higher expectations for the services across the five quality domains measured 17 . Similarly, high satisfaction scores were reported by Auta et al 21 among patients consulting pharmacists at CPs in Jos, Nigeria, citing a better understanding of their conditions postvisit 18 .…”
Section: Barriers Hindering Effective Referral/care Transition Proces...mentioning
confidence: 99%